Multi criteria decision making under single-valued neutrosophic set environment for supplier selection - Firdawati Mohamed,; Nur Aina Syahirah Abdul Shuhaizam,; Nur Nasreen Asharah Mohd Zaki,; Nurul Ain Mohd Rosdi,; Siti Nurul Fitriah Mohamad,; Suziana Aida Othman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The process of selecting suppliers is a crucial decision for organisations and has a substantial effect on enterprises, particularly in industries with extensive and constantly evolving supply chains. In this study, six predetermined criteria are used to evaluate four possible supplier choices under the proposed framework for supplier selection. These criteria include competitive pricing, distance, volume flexibility, technological capabilities, material quality, and complaint handling. This study employs the multi-criteria decision-making (MCDM) technique and single-valued neutrosophic sets (SVNS) to address the challenge of selecting a sustainable supplier with insufficient information. To achieve this, the study uses SVNS-based scoring and accuracy functions. A ranking method, specifically designed for single-valued neutrosophic numbers (SVNN), is used to effectively represent and solve the supplier selection problem. Based on the weight model, the ranking order is A1 > A2 > A4 > A3. Unlike other methods, this technique helps decision-makers effectively communicate imprecise and unclear information. It offers a distinct perspective and approach for MCDM in situations marked by ambiguity. In addition, it allows decision-makers select suppliers that provide exceptional quality and prioritise sustainable business practices.